Efectos generados por los lixiviados del vertedero municipal de la ciudad de Valencia enla calidad del agua superficial y subterránea. año 2012. Programa de manejo de lixiviados. - Bonifaz Andrades, Adriana Guadalupe (2013)
This investigation evaluated the effects generated by municipal landfill leachate from Valencia City in the surface water and groundwaterquality. We considered fourteen parameters suggested by the specialized literature for water quality and fifteen for the leachate. Representative samples of water was take from Valencia stream, artesian well-located 210 m with domestic purposes and the leachates. Previously were six spending gauging liquid for to generate a lineal regression equation that explains the variation of the flow vs. Oxygen dissolved in dry time of year. Using the Watershed Homogeneous Criteria, with climatological datainformation of surrounding stations, was generate for the study area the water balance and get the amount of leachate generated in the landfill. The characterization of surface water and groundwater allowed determine the affectationdegree in its composition due to the migration of leachate. The parameters out of the environmental normative are: Dissolved oxygen, pH, Ammonium, Iron, Cadmium and Lead. The above served to verify the hypothesis: "The leachate from a municipal landfill of Valencia City affects negatively to the surface water and groundwater quality of the sector" From the results obtained are elaborate the proposal: “Leachate Management Program” that contemplate: a Monitoring Red for surface water and groundwaterquality; and a System of Leachate Management to considering the relationship DBO/DQO of leached indicate that easily treatable; This system contemplates the construction of dynamic thickfilter, zeolític camera and infiltration grave.